Phylogeography and population genetics of the white spotted eagle ray, Aetobatus laticeps Gill, 1865, in the Eastern Tropical Pacific - Mateo Vinueza Guarderas; María de Lourdes Torres; María José Pozo Andrade; Adriana Cevallos; Javier Tovar-Ávila; Rossana Maguiño; Daniella Biffi; Carmen González; Sebastián Hernández; Diana A. Pazmiño (PLoS ONE, 2026)
The Eastern Tropical Pacific (ETP) Spotted Eagle Ray, Aetobatus laticeps Gill, 1865, is an understudied species with limited information on its ecology and conservation status. Only in the last 10 years has this lineage been re-described as a distinct species from the formerly widespread Aetobatus narinari species complex (Euphrasen, 1790) (ANSC). The sampling in the studies that divided the ANSC was not geographically balanced, with most individuals (50) collected from the Atlantic and only (5) from the ETP. Given the vast extent and environmental heterogeneity of this region, it is possible that a significant portion of the genus’s genetic variation, and possibly even the presence of undescribed species, is being overlooked. Because eagle rays have relatively low fecundity and are subject to targeted and incidental fisheries, they are highly susceptible to population declines. Consequently, elucidating the genetic diversity, distribution range, genetic variability and interconnectivity of this species is crucial to assess its conservation status correctly. Through a mixed genetic marker approach, we assessed ETP eagle rays’ phylogeny, genetic diversity and phylogeography. First, we confirmed that eagle rays in this region correspond to A. laticeps. Second, we found low levels of genetic variability across all markers, coupled with a high degree of geographic-genetic structure. Finally, our data suggested three potential mechanisms that could explain the population structure we encountered: a) Isolation by distance b) Isolation by philopatry, and c) Isolation by depth. To date, this is the first comprehensive study of the genetic diversity of eagle rays in the Eastern Tropical Pacific, shedding light on a species that has long been overlooked. Our findings suggest that this species is more susceptible to direct and bycatch fishing pressures, as well as other indirect human impacts. Therefore, we recommend a re-evaluation of the conservation status of this species.